2020
DOI: 10.1002/2211-5463.12814
|View full text |Cite
|
Sign up to set email alerts
|

The long non‐coding RNA LOC285758 promotes invasion of acute myeloid leukemia cells by down‐regulating miR‐204‐5p

Abstract: Acute myeloid leukemia (AML) is the second most common type of leukemia worldwide. It was previously reported that expression of the long noncoding RNA LOC285758 is positively associated with AML cell proliferation, but the underlying mechanisms have not previously been reported. Here, we report that LOC285758 expression is higher in clinical AML blood samples and cultured AML cells. miR‐204‐5p was confirmed to be a target gene of LOC285758 by bioinformatics analysis and luciferase assay. LOC285758 overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…2c, d ). These two miRNAs were both negative regulators of AML development and inhibited the growth of AML cells 38 , 39 . The findings indicated that the CD27-AS1/miR-224-5p axis may be one of the ways that CD27-AS1 regulates the growth of AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…2c, d ). These two miRNAs were both negative regulators of AML development and inhibited the growth of AML cells 38 , 39 . The findings indicated that the CD27-AS1/miR-224-5p axis may be one of the ways that CD27-AS1 regulates the growth of AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01268 has been recently described as being upregulated in AML samples [ 52 , 53 ]. In a first work LINC01268 has been described as acting as competing endogenous RNA (ceRNA) via sponging the onco-suppressor miR-217 which in turns inhibits at the post-transcriptional level SOS1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…An upregulation of LINC01268 (therein referred as LOC285758 ) was described also to induce invasion and viability in AML cells by directly sponging miR-204, which inhibited N-Cadherin and TWIST -1 and increased E-Cadherin [ 53 ]. A downregulation of miR-204 in AML was also described by the work of Butrym et al, where decreased serum level of miR-204 have been correlated with a poor prognosis of AML [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-204 expression in AML patients was decreased and was associated with shorter patient survival. Higher expression of this miR was observed in patients after induction therapy and was correlated with complete remission [ 55 ], and its targeting promotes the viability and invasion of AML cells [ 56 ]. Wang et al demonstrated that overexpression of these miRNAs potentiates the sensitivity of AML cells to arsenic trioxide [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent work showed that in breast cancer, miR-204 regulated the expression of key cytokines in tumor cells and reprogrammed immune cells by shifting myeloid and lymphocyte populations, suggesting that this miRNA suppresses tumor metastasis and remodeling the immune microenvironment [ 58 ]. MiR-518b was also reported to function as a tumor suppressor in glioblastoma [ 56 ], esophageal and squamous cell carcinoma [ 59 ].…”
Section: Discussionmentioning
confidence: 99%